Pruning after budburst delays phenology and affects yield components, crop coefficient and total evapotranspiration in Vitis vinífera L. cv. ‘Malbec’ in Mendoza, Argentina - Bustos Morgani, Marianela; Perez Peña, Jorge Esteban; Fanzone, Martín Leandro; Prieto, Jorge Alejandro (Elsevier, 2022)
Late pruning is a field technique that has recently been proposed to mitigate the advance in phenology produced by global warming. However, contrasting effects have been observed depending on the cultivar and the date of pruning evaluated. In this work, our aim was to evaluate the effects of delayed pruning on phenology, vegetative growth, yield components, and crop evapotranspiration in cv. Malbec. During three seasons, winter pruning (WP) was compared to three late pruning treatments: plants pruned at budburst (BB), at 2-3 unfolded leaves (2-3 L) and at 8 unfolded leaves (8 L). Our results showed that late pruning treatments delayed phenology from budburst to veraison the three years of experiment, but harvest date could not be postponed. Plants pruned at 2-3 L and 8 L showed a decrease in vine yield of 17% and 60%, respectively while plants pruned at budburst showed the same yield than control vines. Late pruning treatments did not cause carry over effects on yield formation the following season. Finally, plants pruned at 2-3 L and 8 L reduced annual crop evapotranspiration by 5–10% mainly at the beginning of the cycle, compared to control and BB. Our study provides evidence that late pruning is effective to delay the first phenological stages but it is not as effective to delay the total soluble solids accumulation fixed for harvest, in our conditions.